Analysis of Knowledge Management, Skill and Work Attitude on Employee Performance at PT. Bank BNI Bojonegoro Branch Office - Riena Fitri Andhita Sari; Gendut Sukarno (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the effect of knowledge management, skills, and work attitude on employee performance at the PT. Bank BNI Bojonegoro Branch Office. The sampling technique used was saturated sampling, so the number of samples taken was 40. The analysis technique used in this study is smart partial least squares (PLS). The results of the analysis show that (1) knowledge management has a significant positive effect on employee performance at PT. Bank BNI Bojonegoro Branch Office and (2) skills have a significant positive effect on employee performance at PT. Bank BNI Bojonegoro Branch Office (3) Work attitude has a significant positive effect on employee performance at the PT. Bank BNI Bojonegoro Branch Office.